Oleanolic Acid Acetate Alleviates Symptoms of Experimental Autoimmune Encephalomyelitis in Mice by Regulating Toll-Like Receptor 2 Signaling - Kim, Minju; Lee, Soyoung; Lim, Hyungjin; Lee, Jihye; Park, Ji-Young; Kwon, Hyung-Jun; Lee, In-Chul; Ryu, Young-Bae; Kim, Jeongtae; Shin, Taekyun; Ahn, Ginnae; Rho, Mun-Chual; et al. (Frontiers in Pharmacology, 2020)
Toll-like receptor 2 (TLR2) is expressed by several immune cells in the central nervous system and plays an important role in neuroinflammation. TLR2 upregulation has been reported in multiple sclerosis patients and in experimental autoimmune encephalomyelitis (EAE), a mouse model for multiple sclerosis. Therefore, modulating TLR2 signaling can be an effective treatment strategy against MS. Oleanolic acid acetate (OAA) has antiinflammatory and immunomodulatory effects. Hence, this study aimed to examine the effects of OAA on TLR2 signaling and neuroinflammation in EAE. EAE was induced in C57/BL6 mice using synthesized myelin oligodendrocyte glycoprotein (MOG)35-55 peptide, and OAA was administered daily. Hind limb paralysis and inflammatory cell infiltration were observed in the spinal cords of EAE mice. Moreover, T-cell proliferation was significantly stimulated in splenic cells from EAE mice. The expression of proinflammatory cytokines in the spinal cord was upregulated, and their serum protein levels were increased in EAE mice. Furthermore, upregulation of TLR2 and downstream signaling molecules was observed in the spinal cord. These pathological changes were reversed by OAA treatment. Our results suggest that OAA might have promising therapeutic properties and that the TLR signaling pathway is an effective therapeutic target against multiple sclerosis.